Особливості застосування накопичувачів електричної енергії в системі електропостачання залізниці - Стисло, Богдан Олександрович (НТУ "ХПІ", 2018)
Пульсуючий характер потужності, що споживається в мережі електропостачання залізниці є причиною появи пульсацій напруги в контактній мережі. Це призводить до зниження ефективності енергосистеми. Для компенсації пульсацій потужності в мережі електропостачання залізниці пропонується використання гібридних накопичувачів електричної енергії. Запропоновано застосування двоканальних підсилюють пунктів з відповідною системою управління. В основу математичної моделі покладені дані реальних вимірів.

The pulsating mode of the power consumption in the railroad power supply network is the cause of the occurrence of voltage pulsations in the contact network. This leads to a decrease in the efficiency of the energy system. The purpose of this work is to develop means to improve the quality of the electrical energy of the railroad power supply system and formulate recommendations for their use. To compensate power fluctuations in the electric power supply network of the railway, it is proposed to use hybrid electric energy storage devices. The use of two-channel additional traction power station with an appropriate control system was proposed. The basis of the mathematical model is the data of real measurements. To suppress the power pulsations in the power supply system of the railway, it was proposed to use two-channel additional traction power station. The paper presents DC-DC converter with CF and VF terminals. As a result, dynamic losses are reduced and higher operating frequencies could be achieved. The possibility to transfer power in both directions allows the topology to be applied in high power battery applications. The possibility of using a single low-pass filter for the generation of control signals for both low-frequency and high-frequency channels of system is proven. The use of effective methods of balancing voltage levels in accumulators’ stack makes it possible to reduce the power of losses in the converter by 10-15%.
The features of the use of energy storage devices in the railway power supply system
Keywords: електроживлення залізниці; якість електроенергії; двоканальний підсилюючий пункт; розподілена енергетична система; фільтр низьких частот; розділена комутація; балансування акумуляторів; power quality; distributed energy system; low-pass filter; separated commutation